2015
DOI: 10.3174/ajnr.a4290
|View full text |Cite
|
Sign up to set email alerts
|

Hyperintense Optic Nerve due to Diffusion Restriction: Diffusion-Weighted Imaging in Traumatic Optic Neuropathy

Abstract: Hyperintensity of the optic nerve due to diffusion restriction can serve as a specific imaging marker of traumatic optic neuropathy. When paired with reduced ADC values, this finding may be an important surrogate for visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 14 publications
(13 reference statements)
2
22
0
Order By: Relevance
“…2a) [31]. Traumatic optic neuropathy (TON) can be confirmed using MRI as hyperintensity of the optic nerve due to diffusion restriction can serve as a specific imaging marker and when paired with reduced ADC values, an important surrogate for visual acuity [32].…”
Section: Facial Anatomy and Landmarksmentioning
confidence: 99%
“…2a) [31]. Traumatic optic neuropathy (TON) can be confirmed using MRI as hyperintensity of the optic nerve due to diffusion restriction can serve as a specific imaging marker and when paired with reduced ADC values, an important surrogate for visual acuity [32].…”
Section: Facial Anatomy and Landmarksmentioning
confidence: 99%
“…Accordingly, results of this study were also regarded to be suggestive of disruption in the optic nerve. Despite several number of studies that investigated the relationship between MS and optic nerve disruption on DWI have been conducted (6,16,(21)(22)(23)29), there have not been any previous study in the literature that investigated the changes at the optic nerve head/intraorbital segment in patients with MS. With DWI, there can have difficulties in evaluating the canalicular and intracranial segments of the optic nerve due to anatomical localization, but intraorbital segment and the optic nerve head can be examined with higher precision (30). Seeger et al (30) reported that it is possible to detect optic neuritis, with high sensitivity, in the intraorbital segment without the need for contrast.…”
Section: Discussionmentioning
confidence: 99%
“…VA was converted into a logarithm of the minimum angle of resolution (logMAR) units (On-line Table 3) to provide a numeric scale for statistical analysis. 11,12 Diagnostic performance of the strongest CT predictor derived from the regression analysis was further analyzed by receiver operating characteristic curves after converting the visual outcome into a binary variable (VA Յ LP and VA Ն LP). The data excluded from regression analysis were used as a test set to validate the results because all the patients had admission facial CT scans.…”
Section: Discussionmentioning
confidence: 99%